2019
DOI: 10.3390/su11236607
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Synergies between the Cultural and Tourism Industries: An Efficiency Evaluation Perspective

Abstract: Cultural tourism has received widespread attention for its role in promoting cultural heritage and economic growth. However, there is insufficient research regarding how to verify the synergy between culture and tourism and how to ensure its sustainability in the integration of the cultural and tourism industries (CTI). This study establishes an interdisciplinary composite analytical framework from the perspective of efficiency evaluation. China, a country that has advocated the integration of CTI since 2009, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 61 publications
1
31
0
1
Order By: Relevance
“…Synergy or cooperation is a fundamental principle of sustainable development in a participatory process where stakeholders and the local community can achieve their goals together (Hidayah et al, 2022). Although the concept of synergy is slightly different, it is often associated with the terms integration, coordination and convergence to express a similar trend in two industries (Su et al, 2019). Cetinski et al (2009) studied the synergy between tourism stakeholders in terms of public-private partnerships and demand for tourism at the destination (see also : Omerzel, 2011).…”
Section: Smart Tourism and Stakeholdersmentioning
confidence: 99%
“…Synergy or cooperation is a fundamental principle of sustainable development in a participatory process where stakeholders and the local community can achieve their goals together (Hidayah et al, 2022). Although the concept of synergy is slightly different, it is often associated with the terms integration, coordination and convergence to express a similar trend in two industries (Su et al, 2019). Cetinski et al (2009) studied the synergy between tourism stakeholders in terms of public-private partnerships and demand for tourism at the destination (see also : Omerzel, 2011).…”
Section: Smart Tourism and Stakeholdersmentioning
confidence: 99%
“…Since the two sectors serve different stakeholder groups, they have played different roles in society for a long time for different purposes. People in the tourism industry regard cultural resources as important raw materials for their tourism products to produce tourism-related products and economic wealth ( 53 , 54 ), while people in the cultural management sector cherish these assets because of their intrinsic value and use them with very strict approaches to preserve these samples of cultural resources for the future, with the aim of serving the wider public interest, basically structured around public sector or non-profit organizations ( 55 ).…”
Section: Regeneration Paths Of Qingming Bridge Historic Districtmentioning
confidence: 99%
“…Ma et al analyzed the sustainable livelihoods of households a typical rural tourist site in Wuyuan County, Jiangxi Province, and found that the development of rural tourism with material cultural resources and intangible cultural heritage promoted the transformation of farmers' livelihood strategies, but the development of rural tourism made cultural protection a potential source of farmers' livelihood vulnerability [12]. Su et al established an interdisciplinary composite analytical framework from the perspective of efficiency evaluation, and showed that after the intervention of cultural industry, the technical efficiency of tourism industry has been significantly improved, and there is a synergistic effect between culture and tourism [13]. With the increasingly close integration of tourism and emerging cultural formats, the influence of fashion culture or pop culture on tourist destinations has gradually attracted scholars' attention.…”
Section: Introductionmentioning
confidence: 99%